From Groundwork to Efficient Solar Cells: On the Importance of the Substrate Material in Co‐Evaporated Perovskite Solar Cells. (24th July 2021) - Abzieher, Tobias; Feeney, Thomas; Schackmar, Fabian; Donie, Yidenekachew J.; Hossain, Ihteaz M.; Schwenzer, Jonas A.; Hellmann, Tim; Mayer, Thomas; Powalla, Michael; Paetzold, Ulrich W.
Abstract: Vacuum‐based deposition of optoelectronic thin films has a long‐standing history. However, in the field of perovskite‐based photovoltaics, these techniques are still not as advanced as their solution‐based counterparts. Although high‐efficiency vacuum‐based perovskite solar cells reaching power conversion efficiencies (PCEs) above 20% are reported, the number of studies on the underlying physical and chemical mechanism of the co‐evaporation of lead iodide and methylammonium iodide is low. In this study, the impact of one of the most crucial process parameters in vacuum processes—the substrate material—is studied. It is shown that not only the morphology of the co‐evaporated perovskite thin films is significantly influenced by the surface polarity of the substrate material, but also the incorporation of the organic compound into the perovskite framework. Based on these studies, a selection guide for suitable substrate materials for efficient co‐evaporated perovskite thin films is derived. This selection guide points out that the organic vacuum‐processable hole transport material 2, 2″, 7, 7″‐tetra( N, N ‐di‐p‐tolyl)amino‐9, 9‐spirobifluorene is an ideal candidate for the fabrication of efficient all‐evaporated perovskite solar cells, demonstrating PCEs above 19%. Furthermore, building on the insights into the formation of the perovskite thin films on different substrate materials, a basic crystallization model for co‐evaporated perovskite thin films is suggested. Abstract : The suitability of substrate materials for co‐evaporated perovskite solar cells is commonly assessed via heuristic approaches. Here, a universal guideline for the choice of substrate material is developed by investigating the thin‐film formation of co‐evaporated perovskite absorbers on various substrate materials. The guideline enables a targeted screening of substrate materials based on their surface characteristics enabling efficient all‐evaporated perovskite solar cells.